Emotional changes and Inmunoglobulin A (IgA) after psychological treatment in women victims of domestic violence. - Madrigal, Lucía; Cardenal, Violeta; Téllez, Teresa; Ortiz-Tallo, Margarita; Jiménez, Eugenio (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study was to determine the benefits of a psychological treatment in women victims of mistreatments in psychological health and in the immune system. The participants in this study were 60 women users of the Equality Area of the City Council of Malaga. We set two groups of women up in relation of whether the women attended or not to the given therapy. Psychological variables (self-esteem, depression and anxiety) and levels of Inmunoglobulin A were evaluated before and after the treatment. The results showed differences between all the variables before and after the treatment, with better valuation after the treatment. These differences were not shown in women that did not assist to the therapeutic sessions, and even, the values of depression and immunoglobulin A levels were worse.  We found also differences in the values of these variables when the two groups were compared. Women that received the treatment showed fewer indicators of psychological alterations and higher levels of immunoglobulin A than the women that did not assist to the sessions; in the pre-treatment these differences were not shown. This study enhances the significance of the psychological treatment for psychological and physic health in women victims of abuses.